Divulgação de Matérias Ambientais – Impacto na Informação Financeira da Volkswagen - Oliveira, J.; Azevedo, G.; Borges, F.; Santos (ICAFI 2021 - International Conference on Accounting and Finance Innovation, 2021)
Over the years, we have been facing a significant increase in the disclosure of environmental matters. Companies play a daily and intervening role in the best social and environmental practices. This intervention and concern is mainly due to the maintenance of its image and reputation. Being Volkswagen AG a large company and with a great reputation to maintain, it is interesting to see its behaviour when facing situations that may affect its image and legitimacy. Therefore, this case study assumes as the main objective, to perceive and evaluate the company's reaction to an event with negative environmental impact, which may affect its reputation. To achieve this, we proceed to the analysis of the financial reports, the sustainability reports and some communications from 2014 to 2016, using the method of content analysis given that this study focuses on a qualitative analysis of information. The results of the study show that the company has a great concern with the external perception of the society and, in the face of the emissions crisis, sought to minimize its impacts by assuming the responsibility and applying corrective and compensatory measures.